Under five and infant mortality in Chile (1990-2016): Trends, disparities, and causes of death - Aguilera, Ximena (PLoS One, 2020)
BACKGROUND: Child health has been a health policy priority for more than a century in Chile. Since 2000, new health and intersectoral interventions have been implemented. However, no recent analyses have explored child mortality and equity in Chile, an indispensable input to guide policies towards the achievement of the Sustainable Development Goals, specially, in the context of a deeply unequal country such as many other Latin American countries. Thus, the objectives of this study are to analyze the variations in the risk and the causes of death among Chilean children aged <5 years, to identify the determinants, and to measure inequality of infant mortality from 1990 to 2016. MATERIALS AND METHODS: An observational study was conducted to analyze the Chilean children's mortality from 1990 to 2016 using under five deaths and live births data from the Vital Statistics System. To describe the variation in the risk of death, a time series analysis was performed for each of the under five mortality rate components. A comparative cause of death analysis was developed for Neonatal and 1–59 months’ age groups. The determinants of infant mortality were studied with a descriptive analysis of yearly rates according to mother’s and child factors and bivariate logistic regression models at the individual level. Finally, simple and complex measures of inequality at individual level were estimated considering three-year periods. RESULTS: Regarding under 5 mortality: (i) Child survival has improved substantially in the last three decades, with a rapid decline in under five mortality rate between 1990 and 2001, followed by a slower reduction; (ii) early neonatal mortality has become the main component of the under five mortality rate (50.6%); (iii) congenital abnormalities have positioned as the leading cause of death; (iv) an important increase in live births below 1,000 grs. Regarding infant mortality: (i) birth weight and gestational age are the two most relevant risk factors in the neonatal period, while social variables are more significant for post-neonatal mortality and, (ii) the inequality according to mother’s education has shown a steady decline, with persistent inequalities in post-neonatal period. CONCLUSIONS: The Chilean experience illustrates child health achievements and challenges in a country that transitioned from middle-to high-income in recent decades. Although inequity is one of the main challenges for the country, the health sector by granting universal access was able to reduce disparities. However, closing the gap in post-neonatal mortality is still challenging. To overcome stagnation in neonatal mortality, new and specific strategies must address current priorities, emphasizing the access of vulnerable groups.